Changing Neighborhood Culture: The Case of Kaptanpaşa - Hızlı, Neslinur (ICONARCH International Congress of Architecture and Planning, 2017)
In Istanbul, where many cultures lived together for centuries, it is obvious that there is a very rich housing accumulation. Since the end of the 19th century, living in apartments has become a well-known feature of urban life especially in more cosmopolitan and commercial districts such as Galata, Pera and Şişli. The case of this study, Kaptanpaşa Neighborhood in Şişli, has a heterogeneous social pattern in terms of culture and lifestyle. There are many housing types built in the neighborhood at different times with different lifestyle practices. In Ottoman period, the neighborhood consisted of very few settlements and the large part of the neighborhood was covered with agricultural fields. In the 1960s, there were two large apartment blocks built for İETT employees, which are very important modern building examples both in terms of contemporary Turkish architecture and social state understanding. This process continued with the construction of other settlements and gated community. Today, there are site-style housing types with different typologies located linearly on three separate dead-end streets in the neighborhood. The research aims to answer two fundamental questions; “How does the change of urban spatial composition affect neighborliness relations?” and “Is it possible to maintain neighborhood culture under the influence of changing urban living spaces?” For this purpose, the transformation of neighborhood has been examined in historical context via urban and spatial effects of housing built in different years and existing today. Conceptual and historical information and original data are obtained through author’s personal archive2 , observations at study area and in-depth interviews with residents.